Improving coal permeability using microwave heating technology—A review. (15th April 2020) - Huang, Jinxin; Xu, Guang; Liang, Yunpei; Hu, Guozhong; Chang, Ping
Abstract: Microwave heating is a promising non-aqueous technology in coal seam enhancement. Recently, it has been considered as an alternative technology to hydraulic fracturing and Enhanced Coal Bed Methane recovery, which may be inapplicable due to environmental and geological restrictions. In this paper, a critical review of microwave heating (MH) applications in coal permeability enhancement is presented. The mechanisms of both microwave heating and microwave-induced permeability enhancement are explained. Most of the experimental studies and numerical simulations in the related area are reviewed. The influencing factors for microwave heating/fracturing effect are then discussed in detail. After discussing the challenges in applying microwave on-site, potential field applications were suggested. As no field application is reported till now, further studies, especially experiments in the field-scale are in badly demand to test its technical and economic feasibility.